IOT based Non-Invasive Transcutaneous Bilirubinometer for Jaundice Prediction - Chin, K. L.; Ramli, M.; Halim, N. H. (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2021)
IOT based Non-Invasive Transcutaneous Bilirubinometer is the device that measures the yellowness of the skin (jaundice) by analysing the spectrum of the light reflected from the newborn’s skin based on transcutaneous bilirubin (TcB) where the amount of bilirubin is measured. Jaundice is always occur in infants or newborn where the condition of the infants or newborn like the skins, eyes and other tissues of the baby becomes yellowish. The overall process involved are development of non-invasive bilirubin meter device, the method of non-invasive test conducted for transcutaneous bilirubin then the monitoring process of bilirubin level with automatic data storage of patient in smartphones. This IOT based Non-Invasive Transcutaneous Bilirubinometer device also used infrared (LED green and blue 455-575nm), photodiode (BPW21R) and colour sensor (TCS3200) that can detect the bilirubin level in the blood through the surface skin of the newborn without giving them any discomfort and pain. This device has a new upgradation system by using the MIT software application and IOT Android system that can give the result of the test conducted. The data from the test will be stored on the phone automatically and the user can keep monitoring the condition of the newborns via the phone continuously.